Role of bedrock on stream conductivity and groundwater contribution to streams: a case study from Jhikhu Khola watershed, central Nepal - Nakarmi, G.; Li, T. (Journal of Nepal Geological Society, 1998)
Role of rock formations on water conductivity and groundwater condition contributing to stream flow was examined in the Jhikhu Khola watershed, central Nepal. More than 75% of annual rainfall occurring between June and September which recharges the groundwater. Carbonate rocks are responsible for the higher conductivity values whereas mica schist and quartzite yield little flow with low conductivity during dry season. For better understanding of the water storage capacity of the rock formations, detail studies on distribution of fissures and cavities in the rocks are essential. Application of selected tracer will assist to evaluate flow direction and quantify the rate of flow.